2016
DOI: 10.1101/gr.208173.116
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome fragility is associated with future transcriptional response to developmental cues and stress inC. elegans

Abstract: Nucleosomes have structural and regulatory functions in all eukaryotic DNA-templated processes. The position of nucleosomes on DNA and the stability of the underlying histone-DNA interactions affect the access of regulatory proteins to DNA. Both stability and position are regulated through DNA sequence, histone post-translational modifications, histone variants, chromatin remodelers, and transcription factors. Here, we explored the functional implications of nucleosome properties on gene expression and develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
(110 reference statements)
2
13
0
Order By: Relevance
“…However, the existence of fragile nucleosomes is controversial, since high-resolution mapping by ChIP and tiling microarray reveals scant evidence for histones at yeast promoters (Fan et al, 2010). MNase-sensitive nucleosomes have also been reported in higher eukaryotes (Chereji et al, 2016; Ishii et al, 2015; Iwafuchi-Doi et al, 2016; Jeffers and Lieb, 2016; Mieczkowski et al, 2016; Teif et al, 2014; Vera et al, 2014; West et al, 2014). …”
Section: Introductionmentioning
confidence: 88%
“…However, the existence of fragile nucleosomes is controversial, since high-resolution mapping by ChIP and tiling microarray reveals scant evidence for histones at yeast promoters (Fan et al, 2010). MNase-sensitive nucleosomes have also been reported in higher eukaryotes (Chereji et al, 2016; Ishii et al, 2015; Iwafuchi-Doi et al, 2016; Jeffers and Lieb, 2016; Mieczkowski et al, 2016; Teif et al, 2014; Vera et al, 2014; West et al, 2014). …”
Section: Introductionmentioning
confidence: 88%
“…When the NDRs are wide enough (>150 bp), a common occurrence at open promoters, they might not be truly nucleosome-free, and instead, may harbor highly dynamic nucleosomes, termed ‘fragile’ nucleosomes [ 190 , 191 , 192 , 193 ] ( Figure 5 A, right). Fragile nucleosomes appear to be conserved as they have been identified in promoters of highly expressed genes in many organisms, for example, C. elegans [ 194 ], Drosophila embryos [ 195 ], and mouse Embryonic Stem Cells (ESCs) [ 196 ], and their presence and stability relate to the rate of transcription [ 197 ]. Importantly, in yeast, ‘fragile’ nucleosomes appear to be partially unwrapped nucleosomes resulting from the action of the SWI/SNF-subfamily remodeler RSC and subsequent binding of ‘general regulatory factors’ (GRFs) [ 198 ].…”
Section: Remodelers and Nucleosome Positioning At Enhancers And Promoters In Transcription Regulationmentioning
confidence: 99%
“…Unstable nucleosome-like particles, often associated with promoters of highly expressed genes, have also been found in fission yeast [68], plants [69], C. elegans [70], Drosophila [40], human [71], and mouse ES cells [21,72]. One recent study showed that binding of the PTF FoxA retains nucleosomes at active enhancers but renders them more MNase-sensitive, in part by ejecting the linker histone from chromatin [73].…”
Section: Fragile Nucleosomes At Fission Yeast Plant and Metazoan Prmentioning
confidence: 99%